Effects Of Nigella sativa, Linoleic Acid And Eurycoma longifolia On Rabbit Penile Erection - Sahdom, Rosmiyani (2018)
The Nigella sativa (NS) and Eurycoma longifolia (EL) not plays role in fertility but gastroprotective, anti-tumor, anti-anxiety, anti-microbial, anti-inflammatory, antiparasitic, anti-oxidant and anti-pyretic activities. No previous has thorough investigation on both medicinal plants giving spontaneous erection in penis, while studies claim on their potential as well as their effectiveness on reproduction system. Thus, this study investigated these plant’s effect on penile erection of rabbit. In Nigella sativa treatment, animal was treated with Nigella sativa oil , Nigella sativa microemulsion and Nigella sativa nanoemulsion (NSN) and Eurycoma longifolia (EL). Nigella sativa were administered freshly to the rabbits cause no stability assessment done for this preparation.